Stones from the River - Hegi Ursula : 1946-; Ursula Hegi (New York : Simon & Schuster, 1994)
A dwarf becomes the librarian of a small German town. The work makes her privy to many of the town's secrets and she uses them to set people against each other. It's her way of paying them back for the taunts and humiliations.
Z
1140